Study of Seaweed Kappaphycus alvarezii Explants Growth in the Different Salinity Concentrations - Muhammad Aris; Fatma Muchdar; Rusmawati Labenua (Faculty of Fisheries and Marine Universitas Airlangga, 2021)
HighlightThe best salinity for the thallus growth of K. alvarezii is 32 mg/LThe salinity indicates the osmotic balance of K. alvarezii seaweedThis osmoregulation process affects the nutrient absorption of K. alvarezii seaweedThis study aims to develop the availibility of superior seeds of K. alvareziiAbstract Kappaphycus alvarezii is one of the leading commodities in Indonesian waters. Demand for this commodity is quite high, as reflected in the increasing volume of exports each year. Fulfillment of these demands is obtained from the production of cultivation. Generally farmers get natural seaweed seedlings, namely cuttings from existing seaweed. The continuous use of seeds from nature can cause deterioration in the quality and quantity. Handling the problem of quality deterioration from seaweed seeds originating from nature, can be overcome by multiplying the seeds through tissue culture methods in vitro. In term of tissue culture techniques method, the most important thing to note is environmental parameters. An environment parameter that changes suddenly such as salinity can inhibit the growth of seaweed. Thus, this work is attampting the different salinity treatment on seaweed explants K. alvarezii. This study aims at determining (weight) the explants of K. alvarezii with a comparison of the different salinity levels in the in vitro tissue culture method. The method used in this study was a completely randomized design (CRD) with the different salinity treatments namely 30, 31, 32, 33, and 34 ppt. The results showed that the different salinities influenced the growth rate of K. alvarezii seaweed explants with the best explant growth at the salinity of 31 ppt, while the lowest growth value was obtained at 34 ppt